Amy Wadge and her songwriting scholarship scheme at Lewis School Pengam. Issue 1 (1st April 2021) - Jenkins, Bethan
With a focus on songwriting, this article reports on the place of rock and pop as a means for generating creative output in the current Welsh secondary school curriculum. The article outlines how guidance from industry professionals in addition to a robust and relevant pop and rock curriculum can facilitate pupils accessing employment in the contemporary music industry.